1967
DOI: 10.1071/bi9670103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Fertility and Moisture on Lysis of Fungal Hyphae

Abstract: Live hyphae of 13 different fungi lysed faster (from 2 to 7 days) in a fertile garden soil than in an impoverished wheat-field soil (from 3 to 12 days). Also, rate of lysis was more rapid in wet than in dry soil. Two types of lysis occurred: disappearance of protoplasm and cell wall concurrently, a feature of wet soil; and loss of protoplasm leaving an empty cell wall, as seen in dry soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Unlike soil bacteria, the antagonistic activity of actinomycetes was not always hampered at low soil moisture. Bumbieris and Lloyd detected lysis of fungal hyphae in soil too dry for bacterial activity and concluded that actinomycetes were responsible for the lysis in the dry soils .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike soil bacteria, the antagonistic activity of actinomycetes was not always hampered at low soil moisture. Bumbieris and Lloyd detected lysis of fungal hyphae in soil too dry for bacterial activity and concluded that actinomycetes were responsible for the lysis in the dry soils .…”
Section: Discussionmentioning
confidence: 99%
“…were used as the test fungi. Soil (Urrbrae loam) was obtained from a field under pasture for 5 years (Bumbieris and Lloyd 1967), and contained approximately 8•0 X 10 6 bacteria and 3•0 X 10 6 Actinomycetes per gram as determined by the dilution-plate method. Soil agar (Bunt and Rovira 1955) was used for estimating the bacterial populations, and chitin agar (Lingappa and Lockwood 1962) for Actinomycetes.…”
Section: Methodsmentioning
confidence: 99%
“…After collection the soil was adjusted to 17-18% moisture content and stored in plastic bags at room temperature. The time in days for lysis of 90% of fungal hyphae was observed by a direct method (Lingappa and Lockwood 1963;Bumbieris and Lloyd 1967) . Nutrients were added to soil by one of the following methods: (1) soil was mixed with 0•4% (wjw) glucose, peptone, or blood and bone meal 10 days before addition of fungal hyphae; (2) one drop of a 0•1 % aqueous solution of glucose, ammonium nitrate, peptone, glucose-ammonium nitrate, or distilled water was added simultaneously with fungal hyphae to the surface of soil in a 5-cm Petri dish, and then the same nutrient again added on each of the following 3 days; (3) small disks (5 mm diameter) of either'Czapek-Dox agar (with 0'05% yeast extract, but only 1 % sucrose) or water agar, or sections 1 cm long of native oat grass (Themeda avenacea) , all previously colonized by the test fungi, were placed on soil in 5-cm Petri dishes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation